Use of rhodococcus ruber products in treatment of thermal injury - DOU CHUNYAN; ZHANG GUOYING; ZHANG YI; GE BO (2021)
The invention discloses use of rhodococcus ruber cell walls or rhodococcus ruber cell wall skeletons in preparation of drugs for treating thermal injuries. The thermal injuries comprise burns, scalds,chemical burns and the like. When the rhodococcus ruber products are applied to a subject, the treatment effect on thermal injuries is good, and no side effect is caused. 赤红球菌细胞壁或赤红球菌细胞壁骨架在制备治疗热损伤药物中的用途。所述热损伤包括烧伤、烫伤、化学灼伤等。向受试者施用该赤红球菌产品，对热损伤的治疗效果好，且无副作用。